Mitogenomics of five Olidiana leafhoppers (Hemiptera: Cicadellidae: Coelidiinae) and their phylogenetic implications - Xianyi Wang; Jiajia Wang; Ren-Huai Dai (PeerJ, 2021)
Similar morphological characteristics and limited molecular data of Olidiana resulted in their unknown phylogenetic statuses and equivocal relationships. To further understand the genus Olidiana, we sequenced and annotated five Olidiana complete mitochondrial genomes (mitogenomes). Our results show that Olidiana mitogenomes range from 15,205 bp to 15,993 bp in length and include 37 typical genes (13 protein-coding genes, 22 tRNAs, and 2 rRNAs) and a control region. Their nucleotide composition, codon usage, features of control region, and tRNA secondary structures are similar to other members of Cicadellidae. We constructed the phylogenetic tree of Cicadellidae using the maximum likelihood (ML) and Bayesian inference (BI) methods based on all valid mitogenome sequences. The most topological structure of the obtained phylogenetic tree is consistent. Our results support the monophyletic relationships among 10 subfamilies within Cicadellidae and confirm Iassinae and Coelidiinae to be sister groups with high approval ratings. Interestingly, Olidiana was inferred as a paraphyletic group with strong support via both ML and BI analyses. These complete mitogenomes of five Olidiana species could be useful in further studies for species diagnosis, evolution, and phylogeny research within Cicadellidae.